1984
DOI: 10.1139/y84-066
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in aortic and tail artery reactivity to agonists after streptozotocin treatment

Abstract: In the present study, responses to various agonists in thoracic aorta and tail artery strips, obtained from 4-week streptozotocin (STZ)-treated rats and age-matched controls, were studied. Responses in aorta obtained from diabetic animals to the alpha-agonists, norepinephrine (NE), and methoxamine (MOX), to calcium (Ca2+) and potassium (K+) were found to be depressed relative to control tissue. Responses in tail artery however, were found to be different. While responses to K+ were decreased and to Ca2+ unchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…It has been proposed that this is in part due to altered reactivity of vascular smooth muscle to neurotransmitters and circulating hormones (Weidmann et al, 1979). In an attempt to investigate this hypothesis, the responsiveness of vascular preparations from animals with chemically-induced diabetes to various vasoactive agents has been extensively studied (Brody & Dixon, 1964;Ramanadhan & Tenner, 1984;MacLeod & McNeill, 1985;Agrawal et al, 1987;White & Carrier, 1988). Although the results of these investigations appear to be controversial, previous studies from our laboratory have demonstrated that aortae and mesenteric arteries from male rats with streptozotocin (STZ)-induced diabetes of 12 weeks duration are more responsive to the contractile effects of noradrenaline (NA) than are the corresponding arteries from age-matched control rats (MacLeod, 1985;Harris & MacLeod, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that this is in part due to altered reactivity of vascular smooth muscle to neurotransmitters and circulating hormones (Weidmann et al, 1979). In an attempt to investigate this hypothesis, the responsiveness of vascular preparations from animals with chemically-induced diabetes to various vasoactive agents has been extensively studied (Brody & Dixon, 1964;Ramanadhan & Tenner, 1984;MacLeod & McNeill, 1985;Agrawal et al, 1987;White & Carrier, 1988). Although the results of these investigations appear to be controversial, previous studies from our laboratory have demonstrated that aortae and mesenteric arteries from male rats with streptozotocin (STZ)-induced diabetes of 12 weeks duration are more responsive to the contractile effects of noradrenaline (NA) than are the corresponding arteries from age-matched control rats (MacLeod, 1985;Harris & MacLeod, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although the aetiology of vascular disorders in diabetes is not understood, it has been suggested that alterations in the sensitvity and/or responsiveness of vascular smooth muscle to neurotransmitters and circulating hormones may underlie the functional abnormalities of blood vessels in diabetes [5,6]. In this regard, the responsiveness of isolated vascular preparations from STZ or alloxan-diabetic rats has been studied extensively [7][8][9][10][11][12][13]. Although the results of these studies are somewhat inconclusive, the discrepancies might be attributed to differences in experimental conditions such as techniques for measuring contractile force, expression of contractile force, gender, and severity and duration of diabetes.…”
mentioning
confidence: 99%
“…As a consequence, vascular disease has been considered a complicating feature of the diabetic state (2). Recently, attempts to investigate the functions of vascular smooth muscle in diabetes mellitus were carried out using animal diabetes models, either geneti cally derived (3,4) or chemically induced by alloxan (5-7) or streptozotocin (STZ,8,9) treatment. A significant decrease in pros tacyclin production (10) and an increase in sensitivity to noradrenaline (NA, 11) have been reported in the aorta of diabetic mice and rats.…”
mentioning
confidence: 99%